2010
DOI: 10.1089/jamp.2009.0779
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Anticoagulants Limit Pulmonary Coagulopathy, But Not Inflammation, in a Model of Experimental Lung Injury

Abstract: In conclusion, local treatment with APC, AT, heparin, or danaparoid attenuate pulmonary coagulopathy, but not inflammation, in rats with endotoxemia-induced lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 27 publications
4
60
1
Order By: Relevance
“…In studies reporting on pulmonary coagulation markers, nebulized heparin was found to have a markedly anticoagulant effect in the lungs in the presence of pulmonary infection (35,36) or lung injury (49). In studies reporting on pulmonary inflammation, nebulized heparin also inhibited pulmonary inflammation in the presence of pulmonary infection (35,36) or lung injury (43,44), and in two studies using an inhalation trauma model (40,41).…”
Section: Heparinmentioning
confidence: 95%
See 4 more Smart Citations
“…In studies reporting on pulmonary coagulation markers, nebulized heparin was found to have a markedly anticoagulant effect in the lungs in the presence of pulmonary infection (35,36) or lung injury (49). In studies reporting on pulmonary inflammation, nebulized heparin also inhibited pulmonary inflammation in the presence of pulmonary infection (35,36) or lung injury (43,44), and in two studies using an inhalation trauma model (40,41).…”
Section: Heparinmentioning
confidence: 95%
“…Nebulized APC attenuated pulmonary coagulopathy in studies using pulmonary infection models (35,36) and studies using lung injury models (47,49). Nebulized APC was associated with anti-inflammatory effects in two out of the three studies in animals with lung injury (47,48), but not in studies in animals with a pulmonary infection (35,36).…”
Section: Apcmentioning
confidence: 97%
See 3 more Smart Citations